2019
DOI: 10.1021/acsami.9b08318
|View full text |Cite
|
Sign up to set email alerts
|

Flower-like Mn-Doped Magnetic Nanoparticles Functionalized with αvβ3-Integrin-Ligand to Efficiently Induce Intracellular Heat after Alternating Magnetic Field Exposition, Triggering Glioma Cell Death

Abstract: Flower-like-shaped manganese-doped a v b 3integrin-ligand-functionalized SPIONs efficiently induce intracellular heat after AMF-exposition triggering cell death in a glioma cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 62 publications
2
39
0
Order By: Relevance
“…In this study, the SPION zeta potential was −10 mV, a value that might not favor the SPION internalization by cells [81]. Another study that synthesized aminosilane-coated SPION, they were submitted to low frequency (1.16 uT and 350 kHz) and a single MHT application for 30 min, showing 30% of K7M2 cells viability by BLI 24 h after finished the therapy [34], and others studies that used single MHT therapy application displayed efficiency superior than 50% [32,35].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In this study, the SPION zeta potential was −10 mV, a value that might not favor the SPION internalization by cells [81]. Another study that synthesized aminosilane-coated SPION, they were submitted to low frequency (1.16 uT and 350 kHz) and a single MHT application for 30 min, showing 30% of K7M2 cells viability by BLI 24 h after finished the therapy [34], and others studies that used single MHT therapy application displayed efficiency superior than 50% [32,35].…”
Section: Discussionmentioning
confidence: 68%
“…Another studies in vitro using U-87MG cells and employing multiple MHT applications, used SPION with 106.2 nm of diameter submitted to AMF (750 kHz; 200 Gauss), and four days of MHT applications (1 per day during 2 h) showing 50% efficiency after the first MHT application and 80% after three days indicating the importance of latency period for MHT therapeutic efficacy analysis [30]. The precaution adopted in our study of two days latency for MHT efficiency analysis, was very important, because during this latency period it is possible the occurrence of cell death by membrane permeabilization or rupture, increased reactive oxygen species or heat shock protein (Hsp) expression [32]. Others studies that used two MHT applications did not showed significant differences in efficiency between first and second MHT applications, their evaluations occured right after the last MHT application within 30 min between applications [28,29].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…(B) Heat is produced via hysteresis losses and Brownian relaxation (a process in which frictional heating is generated by the physical rotation of the magnetic particle). [193] Preclinical Human GBM (U87-MG) Magnetic iron oxide nanoparticles stabilized with carboxymethylcellulose Fernandez et al [183] Preclinical Human GBM (U87-MG) Manganese-doped ferrite nanoparticles Grauer et al [204] Clinical GBM Superparamagnetic iron oxide nanoparticles Gupta et al [172] Preclinical Rodent Glioma (C6) Stevioside-coated iron oxide nanoparticles (STE-Fe 3 O 4 ) Pandey et al [202] Preclinical Human GBM (U87-MG) Iron Platinum alloy nanoparticles (FePt NP) Rego et al 2019 [171] Preclinical Rodent glioma (C6) Aminosilane-coated superparamagnetic iron oxide nanoparticles Shi et al [190] Preclinical Human GBM (U87-MG); rodent glioma (C8-D1A)…”
Section: Mhtmentioning
confidence: 99%
“…As natural carrier systems, EVs present low immunogenicity, low toxicity, stability in the bloodstream, and efficient cell uptake due to their endogenous cellular tropism [ 13 ]. Their ability to mediate intercellular communication, especially in brain tumor progression, allows their use as a promising therapeutic and diagnostic tool [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], including the challenging treatment of gliomas [ 22 , 23 , 24 , 25 , 26 , 27 ]. Gliomas are the most frequent intrinsic tumors of the central nervous system and, by following the 2016 World Health Organization (WHO) update, encompass two principal subgroups: “nondiffuse gliomas”, showing a more circumscribed growth pattern (WHO grade I), and diffusely infiltrating gliomas (WHO grade II–IV), arising from glial cells or glial precursors [ 28 ].…”
Section: Introductionmentioning
confidence: 99%